Pengaruh Model Pembelajaran Direct Teaching dalam Pembelajaran Passing Atas pada Siswa - Aep Novia (STKIP Muhammadiyah Kuningan, 2019)
The aim of the research was to determine the effect of using a tactical approach to volleyball's passing skills on class VIII male students of SMP Negeri 1 Ciniru Kuningan District Academic Year 2018/2019. The method used in this research is the experimental method. The population in this study were all male students of class X of SMA Negeri 1 Ciniru Kuningan District in the 2018/2019 school year as many as 28 students. Sampling in this study was taken by purposive random sampling technique, then class randomly determined which learning using models direct teaching. After the drawing was done, it was obtained by class X MIPA 2 as an experimental class as many as 28 students. Based on the results of calculations and data analysis, it can be concluded that: There is a significant effect of the influence of Direct Teaching-Learning Model on Upper Passing Learning in Class X Students of SMA 1 Ciniru, Kuningan District, Academic Year 2018/2019.